Genomic insights into a novel species Rhodoferax aquaticus sp. nov., isolated from freshwater. Issue 8 (16th August 2020) - Li, Taihua; Zhuo, Ye; Jin, Chun-Zhi; Wu, Xuewen; Ko, So-Ra; Jin, Feng-Jie; Ahn, Chi-Yong; Oh, Hee-Mock; Lee, Hyung-Gwan; Jin, Long
Abstract : A novel non-phototrophic member of the genus Rhodoferax was obtained from freshwater. The purpose of this study was to analyse the genome of a nonphototrophic strain and propose a new species based on its phylogenetic, genomic, physiological and chemotaxonomic characteristics. The results of phylogenetic analysis based on 16S rRNA gene sequences supports that the strain, designated Gr-4 T, has a close relationship to the genus Rhodoferax . The observed average nucleotide identity (ANI) and digital DNA–DNA hybridization (dDDH) values between strain Gr-4 T and its closest related strains were 72.3–74.6 % and 21.9–22.8 %, respectively. These values were much lower than the species separation thresholds for ANI or dDDH of 95–96 and 70 %, respectively, and in fact fall in the intergeneric range. Strain Gr-4 T does not contain RuBisCO-related genes, but does contain GS/GOGAT pathway-related genes enabling nitrate ammonification. A polyphasic study and a genomic-level investigation were done to establish the taxonomic status of strain Gr-4 T . Based on the phylogenetic, genomic and physiological differences, it is proposed that the isolate be classified to the genus Rhodoferax as Rhodoferax aquaticus sp. nov. with isolate Gr-4 T (=KCTC 32394 T =JCM 19166 T ) as the type strain.